STRATEGI PEMBELAJARAN AKIDAH AKHLAK DALAM MEMBENTUK JIWA LEADERSHIP SISWA KELAS 8 DI MTS HIDAYATUL MUBTADIâ€™IN TASIKMADU MALANG - Muchsin Ghozali; Muhammad Fahmi Hidayatullah; Atika Zuhrotus Sufiyana (VICRATINA, 2022)
Character formation has been implemented in the current education system, but there are still many problems that cause the weakness of positive characters in the world of education. One of them is the character of the leadership, where there are still many of us who are not aware of the importance of the leadership character in life. Within the scope of education, Akidah Akhlak teachers become facilitators in the formation of leadership character. From the implementation of Akidah Akhlak subjects which are poured into religious activities at MTs Hidayatul Mubtadi'in Malang, it can be used as a strategy in forming the character of the student's leadership spirit.Â Based on the research that has been carried out, it is found that the design of aqidah moral learning in shaping the leadership spirit of students is to implement religious activities such as dhuha prayer, reciting the Koran and tahlil together every morning. As for the implementation of moral aqidah learning in shaping the leadership spirit of students, namely by using the assignment method to make students have a sense of responsibility and discipline. Meanwhile, the evaluation of moral aqidah learning in shaping the leadership spirit of students has been carried out. The teacher's efforts to evaluate the learning of moral creed at Mts Hidayatul Mubtadi'in have been carried out but have not run optimally, there are still some evaluations that have not been carried out properly by Akidah Akhlak teachers at Mts Hidayatul Mubtadi'in Malang.